An Overview on Object Detection and Recognition - Raviteja, N; Lavanya, M; Sangeetha, S (International Journal of Computer Sciences and Engineering, 2020)
The main intent of enhancing the present system of object detection is to enhance its productivity and improve the detection accuracy. The method initializes a model in a way to store the background pixels and to compare each frame pixels with the same model background pixels. The intention is to separate the background pixels with the foreground moving pixels to improve the ability to detect the object in the foreground. An improved object detection algorithm based on “Gaussian mixture model” and “three-frame difference method”. This three-frame difference method uses a dynamic segmentation threshold and edge detection technology to solve the problem of illumination mutation and discontinuity of target edge.